Correlation of time trends of air pollutants, greenspaces and tracheal, bronchus and lung cancer incidence and mortality among the adults in United States - Zhao, Jia; Ren, Ruihang; Beeraka, Narasimha M.; PA, Mahesh; Xue, Nannan; Lu, Pengfei; Bai, Wenhua; Mao, Zhihan; PR, Hemanth Vikram; Bulygin, Kirill V.; Nikolenko, Vladimir N.; Fan, Ruitai; et al. (Frontiers in Oncology, 2024)
Background: Tracheal, Bronchus, and Lung (TBL) cCancer continues to represent the majority of cancer-related incidence and mortality in the United States (U.S.). While air pollutants are considered essential risk factors, both global and national average concentrations of major harmful air pollutants have significantly decreased over the decades. Green space may have a beneficial effect on human health.We obtain data on national and state-level burden of TBL cancer, the annual average concentration of main air pollutants, and levels of green spaces in 2007, 2013, and 2019. According to generalized estimating equation (GEE), we examine the associations among incidence and mortality of TBL cancer, air pollutants, and TBL cancer, air pollutants and greenspaces, representinged by the Normalized Difference Vegetation Index (NDVI) in different age groups with models adjusted with meteorological, and socio-demographic and Human development Index (HDI). We observed additional effects of the interaction between the NDVI, Ozone, PM2.5, and other factors, which helped us to interpret and understand our results.. Also, we collated states that witnessed net increments in forest coverage and conducted the same analysis separately.Results: After accounting for meteorological factors and socio-demographic variables iIn our analysis, the majority of associations between NDVI and air pollutants with TBL cancer incidence and mortality remained significantly positive, particularly noticeable among individuals aged 20 to 54. However, our findings did not explore air pollution as a potential mediator between greenspace exposure and TBL cancer. While the associations of PM2.5 with TBL cancer incidence and mortality remained positive, the other four pollutants showed positive but statistically insignificant associations. Our interaction analysis yielded that there were positive associations between NDVI and ozone, PM2.5, and tobacco use. Max NDVI acts as a protective factor along with high HDI. Additionally, PM2.5 and HDI also showed a negative association. Our interaction analysis revealed positive associations between NDVI and ozone, PM2.5 and tobacco use, as well as negative associations between maximum NDVI and HDI, PM2.5 and HDI, and educational level with TBL cancer rates.